Recent Progress on High-Entropy Films Deposited by Magnetron Sputtering - Mohamed El Garah; Pascal Briois; Frederic Sanchette (Crystals, 2022)
High-entropy films (HEFs) are of considerable interest in surface engineering applications due to their superior properties, such as good corrosion resistance, good thermal stability and excellent high temperature oxidation. Recently, the scientific community has seen an increasing development of the multicomponent coatings, improving their properties compared to conventional films. Technically, different strategies have been exploited to fabricate HEFs. Magnetron-sputtered HEFs have made significant advancements in this field. HEFs have various applications given their interesting performances. This article overviews the development and the outcome of HEFs prepared using the magnetron sputtering technique. The classification of HEFs is reported. The effect of magnetron sputtering parameters on the microstructural, mechanical, electrochemical and thermal properties of HEFs is also discussed. Applications of HEFs are reported in the last section.